Aggressive driving behaviour: a forensic psychological perspective - Ball, Laura (2018)
This thesis provides an investigation into aggressive driving behaviour, from a Forensic Psychological perspective. The methods used include a systematic review, two quantitative research studies, and a psychometric critique. A systematic review and meta-analysis of the relationship between a measure of driving anger, the Driving Anger Scale (DAS; Deffenbacher, Oetting & Lynch, 1994), and various aggressive driving outcomes showed a strong positive correlation. However, the validity of this finding is hampered by the extensive use of self-report questionnaires, as opposed to real-world driving behaviours, to measure aggression on the roads. The first empirical research study investigated the relationship between personality characteristics (including driving anger) and aggressive driving outcomes. The results showed that three variables accounted for more than half of the variance in self-reported aggressive driving behaviour. These were a tendency toward physical aggression, the progress impeded aspect of driving anger, and psychopathic tendencies. The findings provide ideas for future research, and intervention to reduce aggressive driving behaviours. The second research study expanded on this, and considered the impact of inattentive responding on outcomes for online surveys, and how these may relate to the driving aggression literature. This was enabled by the discovery that around a third of respondents to a survey failed instructional manipulation checks; inclusion of these participants in analysis obscured the results found in the first study. The findings are discussed in terms of practical implications for researchers. A psychometric critique of the Propensity for Angry Driving Scale (PADS; DePasquale, Geller, Clarke & Littleton, 2001) is also presented. This raised questions about the reliability and validity of the PADS, which will be of interest to researchers considering driving anger and aggression in the future. The findings from each methodology are finally considered together, with a discussion of the implications for the field of aggressive driving research.